The Impact of the Covid-19 Pandemic on the Learning Methods of Health Students Majoring in Radiology and Pharmacy - Utomo, Slamet; Utami, Lucky Restyanti Wahyu; Utami, Rose Malinda Andamari Wahyu (Jurnal EduHealth, 2025)
There have been changes in learning methods in Indonesia due to the Covid-19 pandemic with the implementation of limited face-to-face meetings, including in healthcare institutions. This study aims to determine the impact of the Covid-19 pandemic on the learning methods of healthcare students, especially radiology students at Widya Husada University Semarang and pharmacy students at Kendal College of Health Sciences. The type of research used is quantitative research conducted on radiology students at Widya Husada University Semarang and pharmacy students at Kendal College of Health Sciences who entered lectures in 2020 using an electronic questionnaire. The results of the study obtained regarding the impact of the Covid-19 pandemic on the learning methods used by radiology students at Widya Husada University Semarang are known to be carried out online for theoretical learning with a percentage of 56% and practical learning is carried out in a hybrid manner with a percentage of 55.5%. Meanwhile, the impact of the Covid-19 pandemic on the learning methods of pharmacy students at Kendal College of Health Sciences in theoretical learning is carried out online with a percentage of 44% and practical learning is carried out offline with a percentage of 44.5%. The learning methods used at both institutions are limited face-to-face, while adhering to health protocols as recommended by the government.